An exploration into the applicability of school principals' training on the principals' leadership practices in Finland - Kakon Montua Ajua, Shantal (2012)
Quality leadership preparation has been shown to have positive influences on leadership practices of graduates. With five formal categories of leadership training programmes in the decentralized Finnish educational system, little is known about the leadership practices of graduates. This study explored the applicability of training on principals’ self-assessed leadership practices in Central Finland. Eight semi-structured individual interviews were conducted with principals from schools in and around the municipality of Jyväskylä. Purposive sampling was used as all participants had taken the advanced educational leadership training at the University of Jyväskylä in addition to other training programmes. An inductive content analysis approach was used for data analysis. The findings indicated that besides personal experiences, knowledge gained from theory, practice, leadership and networking constitute major sources of principals’ leadership practices. Training positively enhances the practices of school principals, as they become more competent and able to practice varied leadership styles with a trend towards visionary, collaborative, shared, visibility and transformational leadership styles in schools. School diversity, time constraint, poor student behaviours, future uncertainties resulting from the decline of the student population threaten the position of principals. They however strive to remain effective under such circumstances by applying knowledge acquired from organizational theories, leadership models, strategic planning and effective communication. Nevertheless, principals need additional training to better appreciate and manage future challenges, implement modern teaching methods and promote professional development in their schools. To improve the training, certain programme attributes such as quality and methods of course delivery, management of human and financial resources, creating and sustaining local and international collaborations with other training institutions need to be improved.